Services and Collections Gathered Near the User: Helsinki University Library and its Present Building Projects - Gustafsson, Dorrit (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
As the National Library of Finland, founded 1640, the Helsinki University Library requires adequate space and this is something we have lacked for the last 60 years. Our main effort over the last decades has been to concentrate our services and collections in one area to form a Library complex. The only way to do it is to renovate old above ground and to build new underground and then try to join them.